Effects of Microbial Organic Fertilizer, Microbial Inoculant, and Quicklime on Soil Microbial Community Composition in Pepper (Capsicum annuum L.) Continuous Cropping System - Chengfu Zhang; Limin Zhang; Yang Cao; Sunjian Zhang; Chao Hou; Chaosheng Zhang (Horticulturae)
The additions of microbial organic fertilizer (MOF), a microbial inoculant (MI), and quicklime (Q) are considered to be sustainable practices to restore land that has been damaged by continuous cropping of pepper (Capsicum annuum L.). However, the combined effects of these three additives on pepper yield, soil chemical properties, and soil microbial communities were unclear. The experimental design consists of 13 treatment groups: the untreated soil (control); soil amended solely with three treatments for each of MOF (1875–5625 kg ha−1), MI (150–450 mL plant−1), and Q (1500–4500 kg ha−1); and soil amended with combinations of MOF, MI, and Q at three comparable concentrations. A significant increase in pepper fruit diameter, length, yield, and soil available nitrogen, phosphorus, and potassium contents occurs upon exclusive and combined applications of MOF, MI, and Q. Pepper yield was greatest (29.89% more than control values) in the combined treatment with concentrations of 1875 kg ha−1 MOF, 150 mL plant−1 MI, and 1500 kg ha−1 Q. The application of Q increased soil pH and reduced soil–fungal richness. The application of MOF, MI, and Q increased the relative abundance of bacterial genera and the complexity of bacterial and fungal co-occurrence networks compared with control levels. The combined application of MOF, MI, and Q resulted in the greatest microbial network complexity. A Mantel test revealed the key role of soil available nitrogen content and bacterial diversity in the regulation of pepper growth and yield. We conclude that the combined application of MOF, MI, and Q improves soil nutrient availability and modifies soil microbial community composition, significantly promoting plant growth and pepper yield during continuous cultivation.